PENGEMBANGAN E-LKPD BERBASIS P5 CEGAH ANEMIA DENGAN PANGAN SEHAT SEBAGAI UPAYA DUKUNG CEGAH STUNTING - Sintiani Burhan, Deys; Nusantari, Elya; Solang, Margaretha; S. Kumaji, Syam; Maryati Yusuf, Frida (Jurnal Biogenerasi, 2025)
This study aims to develop an Electronic Student Worksheet (E-LKPD) based on the Pancasila Student Profile Strengthening Project (P5) with the theme "Prevent Anemia with Healthy Food to Support Stunting Prevention" at SMA Negeri 1 Suwawa. The development model used is ADDIE, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interviews, questionnaires, and validation sheets involving subject matter experts, media experts, and students. The practicality results showed positive responses from students (90%) and teachers (86.66%), with learning implementation reaching over 90%. The E-LKPD was found to be not only interactive and contextual but also aligned with 21st-century learning demands and capable of fostering students’ character and entrepreneurial skills. Although still limited to a small-scale trial, this E-LKPD demonstrates great potential for improving the quality of learning and students’ nutritional awareness, particularly in efforts to prevent anemia and stunting.